Optimization of spray operation parameters of unmanned aerial vehicle confers adequate levels of control of fall armyworm (Spodoptera frugiperda) - Ying Liu; Ying Liu; Xiao Liang; Xiao Liang; Chunling Wu; Chunling Wu; Xingkui An; Xingkui An; Mufeng Wu; Mufeng Wu; Zihua Zhao; Zhihong Li; et al. (Frontiers in Plant Science)
IntroductionThe fall armyworm (FAW), Spodoptera frugiperda, is a serious threat to maize production. Unmanned aerial vehicles (UAVs) represent a promising method for controlling FAW outbreaks. Given that FAW larvae primarily feed inside the maize whorl, we hypothesized that the efficacy of insecticide application depends on droplet density and coverage rate on the upper maize canopy.MethodsThis study evaluated the effects of spray operation parameters—including three flight heights (2.0, 2.5, and 3.0 m), three spray volumes (30.0, 37.5, and 45.0 L ha-1), and two nozzle types (XR11001VS and XR110015VS)—on droplet deposition distribution in maize canopies. Additionally, the control efficacy of 35% chlorantraniliprole water dispersible granules (WDG) against FAW was assessed over three consecutive years (2019-2021) to determine its correlation with droplet deposition.ResultsResults indicated that flight height, spray volume, and nozzle type significantly influenced droplet deposition distribution. Two treatments—XR110015VS nozzle with 37.5 L ha-1 spray volume at 2.5 m flight height and XR110015VS nozzle with 45.0 L ha-1 spray volume at 2.5 m flight height—achieved the highest droplet density, optimal coverage rate on the upper maize canopy, and the lowest damage index, confirming our hypothesis. These treatments also demonstrated comparable FAW control efficacy to traditional electric air-pressure knapsack sprayers.DiscussionThe findings provide practical insights for optimizing UAV-based insecticide applications to improve FAW management in maize production systems.